Hypertrophic and strength responses to eccentric resistance training with blood flow restriction: A pilot study - Pope, Z. K.; Willardson, J. M.; Schoenfeld, B. J.; Emmett, J. D.; Owen, J. D.; Loenneke, J. P. (International Journal of Sports Science and Coaching, 2015)
Research examining exercise with blood flow restriction (BFR) has indicated positive findings for the use of this novel training modality in both health and performance-related outcomes. However, eccentric resistance training combined with BFR has yet to be fully examined. Therefore, the objective of this pilot study was to investigate the muscular strength and hypertrophic responses before and following a training intervention involving resistance exercise utilizing only eccentric muscle actions with or without BFR. Eighteen resistance-trained males were randomly assigned to one of three training conditions following pre-testing measures: eccentric resistance training only, eccentric resistance training with BFR, and a control training group. Our findings suggest that four weeks of submaximal eccentric resistance training performed to repetition failure, with or without BFR, may represent alternative means of obtaining increases in muscle cross-sectional area (CSA) in resistance-trained males. Although the addition of BFR did reduce training volume, it did not result in superior adaptations. ABSTRACT FROM AUTHOR